An Automated Two‐dimensional Pairwise form Registration Method for Pair‐matching of Fragmented Skeletal Remains1. Issue 6 (10th April 2018) - Lynch, Jeffrey James
Abstract: This study introduces an automated pairwise method for osteological pair‐matching of fragmented skeletal remains using two‐dimensional fragmented outlines extracted from photographs. The form data are used in pairwise iterative closest point registrations with rigid transformations. A modified version of the average Hausdorff distance is calculated to remove any coordinate correspondences with outline fracture margins, which allow the distance analysis of fragmented outlines. A dilation modification to the Hausdorff distance is proposed creating a greater separation between true‐ and false‐pairs. The sample consists of 122 calcanei (61 pairs) from the UI‐Stanford collection. Performance statistics are provided for simulated fragmented and complete assemblages. Results indicate up to 98% accuracy for fragmented and complete assemblages. The dilated Hausdorff distance performed similarly across assemblages, but showed a slight decrease in performance for the complete assemblage. This approach provides a useful short listing tool to reduce the number of visual comparisons required in large commingled assemblages.